Microglia Function on Precursor Cells in the Adult Hippocampus and Their Responsiveness to Serotonin Signaling - Turkin, Andrei; Tuchina, Oksana; Klempin, Friederike (Frontiers in Cell and Developmental Biology, 2021)
Microglia are the resident immune cells of the adult brain that become activated in response to pathogen- or damage-associated stimuli. The acute inflammatory response to injury, stress, or infection comprises the release of cytokines, and phagocytosis of damaged cells. Accumulating evidence indicates chronic microglia-mediated inflammation in diseases of the central nervous system, most notably neurodegenerative disorders, that is associated with disease progression. To understand microglia function in pathology, knowledge of microglia communication with their surroundings during normal state, the release of neurotrophins and growth factors in order to maintain homeostasis of neural circuits is of importance. Recent evidence shows microglia interact with serotonin, the neurotransmitter crucially involved in adult neurogenesis, and known for its role in antidepressant action. In this chapter, we illustrate how microglia contribute to neuroplasticity of the hippocampus, and interact with local factors, e.g. BDNF, and external stimuli that promote neurogenesis. We summarize the recent findings on the role of various receptors in microglia-mediated neurotransmission, and particularly focus on microglia’s response to serotonin signaling. We review microglia function in neuroinflammation and neurodegeneration, and discuss their novel role in antidepressant mechanisms. This synopsis sheds light on microglia in healthy brain and pathology that involves serotonin, and may be a potential therapeutic model by which microglia play a crucial role in the maintenance of mood.